PROSES JAKSA PENELITI BERKAS PERKARA DALAM MENENTUKAN TERSANGKA BARU PADA TINDAK PIDANA KORUPSI - Rudi (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2022)
Prosecutors Research case files have a very important role in the completion of a criminal act of corruption, namely conducting a formal completeness check, which includes everything related to formalities/requirements, investigation procedures that must be accompanied by a warrant, minutes, court permits/approvals. Although it has regulated the control of criminal acts of corruption, in reality in taking action against the perpetrators of criminal acts of corruption, not all perpetrators of crime are made suspects in the case file. The purpose of this study is to determine the role and process of the Prosecutor for Research in Case Files in making, controlling and resolving all kinds of legal problems that occur today, especially in the field of corruption. This research is a normative legal research using a legal and conceptual approach, with primary legal materials and secondary legal materials. The results of the study indicate that the process of the Prosecutor of Case Research in determining new suspects in corruption cases must be followed by a pattern or mechanism of case title